Justiça do trabalho e produtividade no Brasil: Checando hipóteses dos anos 1990 e 2000 - André Gambier Campos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– This text presents a set of empirical evidence to "test" some hypotheses about the impacts of Labor Justice on labor productivity. Hypotheses that this justice would encourage opportunistic and immediatist behaviors of employers and workers. And these behaviors would result in noncompliance with labor contracts (something concerning to the problem of informality), early termination of these contracts (something related to the problem of turnover), as well as losses for labor productivity (the central focus of analysis of this text). The empirical evidence presented here shows that these hypotheses, which concern to opportunistic and immediatist behaviors, seem to be confirmed mainly by the behavior of employers. After all, from temporal and monetary perspectives, they seem to have something to gain, either with the postponement of credit payments or with the mitigation (or discount) of these payments. In turn, by the workers' side, they seem to have something to lose with both phenomena (with the postponement and the mitigation of credit payments).
Keywords: K31; K40; K49; 330; Labor Justice; labor productivity